Risk factors for anorexia nervosa: three integrated case-control comparisons. - Fairburn, C; Cooper, Z; Doll, H; Welch, S (American Medical Association, 1999)
BACKGROUND: Many risk factors have been implicated in the development of anorexia nervosa. Little is known about their relative contributions, nor in most cases is it clear whether they are specific to anorexia nervosa or risk factors for all eating disorders or for psychiatric disorder in general. METHODS: We used a case-control design involving the comparison of 67 female subjects with a history of anorexia nervosa with 204 healthy control subjects, 102 subjects with other psychiatric disorders, and 102 subjects with bulimia nervosa. A broad range of risk factors was assessed by interview. RESULTS: The subjects with anorexia nervosa and the healthy controls differed in their exposure to most of the putative risk factors. There was no greater exposure to factors that increased the likelihood of dieting, once the influence of other classes of risk factors had been taken into account. Premorbid perfectionism and negative self-evaluation were especially common and more so than among the general psychiatric controls. Parental obesity and an early menarche, together with parental psychiatric disorder, distinguished those with bulimia nervosa from those with anorexia nervosa. CONCLUSIONS: There appears to be a broad range of risk factors for anorexia nervosa and bulimia nervosa, some of which are shared with other psychiatric disorders. Factors that increase the likelihood of dieting seem to have more important influence as risk factors for bulimia nervosa than anorexia nervosa. Perfectionism and negative self-evaluation appear to be particularly common and characteristic antecedents of both eating disorders.